Actitudes, prácticas y conocimiento de las madres en las reacciones post vacuna. - Diaz Diaz, Jhonny Gustavo (My University, 2024)
Vaccination is a key measure for preventing childhood diseases; however, post-vaccination reactions can cause concern among mothers. In this context, this study describes and evaluates the attitudes, practices, and knowledge of mothers regarding post-vaccination reactions in children under 5 years of age within a specific community, as well as identifies gaps that affect vaccine acceptance. This research study is descriptive, prospective, and uses a non-experimental quantitative approach, since data were collected at a specific point in time without manipulating the results. A total of 125 mothers from a rural health center participated, and a validated questionnaire was administered to them. The results indicate that greater knowledge is associated with more favorable attitudes toward immunization. On the other hand, a lack of adequate information may lead to inadequate practices in the management of post-vaccination reactions. Consequently, these findings highlight the need to implement educational strategies that strengthen maternal confidence in vaccination and promote child health
La vacunación es una medida clave para prevenir enfermedades infantiles; sin embargo, las reacciones post vacunales pueden causar preocupación en las madres. En este contexto, este estudio describe y evalúa las actitudes, prácticas y conocimientos de las madres sobre las reacciones post vacunas en los niños menores de 5 años en una comunidad específica, así como identifica brechas que afectan la aceptación de la vacunación. El presente estudio de investigación es de tipo descriptivo, prospectivo, con enfoque cuantitativo no experimental, puesto que los datos se obtuvieron en un momento específico sin manipular los resultados. Participaron 125 madres en un centro de salud rural, a quienes se le aplicó un cuestionario validado. Los resultados indican que un mayor conocimiento está asociado con actitudes favorables hacia la inmunización. Por otro lado, la falta de información adecuada puede llevar a prácticas inadecuadas en el manejo de reacciones post vacunales. En consecuencia, esto evidencia la necesidad de implementar estrategias educativas que fortalezcan la confianza materna en la vacunación y promueva la salud infantil.
Keywords: VACUNACIÓN; REACCIONES POST VACUNALES; CONOCIMIENTO; SALUD